Specialist Peer Mentoring of Autistic University Students - Thompson, Craig Lee (Curtin University, 2020)
This thesis aimed to explore the experiences of autistic university students participating in their studies supported by specialist peer mentoring and the effect this mentoring had on them, their mentors, and their parents. Specialist peer mentors received training to facilitate a successful partnership between mentors and autistic students which improved participation at university and social competence. Specialist peer mentoring also improved the relationships between the autistic student’s parents and their mentors.